(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The research aims to statement the main obstacles that prevent the application of total quality management (TQM) in a number of Iraqi service organizations, and by one organization in each of the sectors (health, finance, education, higher education, tourism), which are, (Al-Yarmouk Teaching Hospital, Rafidain Bank/ Branch of Hay Al-Arabi Al-Jadid, Al-Karkh/1 Directorate of Education, College of administration and Economics/ Baghdad University, International Palestine Hotel). The research also, tries to classify the priority of the obstacles depending on the type of service organization surveyed. And diagnoses the extent to which or the difference of the research sample members views on the order of obstacles of TQM, and also proposes a set of solutions to address these obstacles. The research adopted the questionnaire as a tool to analyze the practical side, which was distributed to the leaders in each organization and by (80) questionnaire to represent a research sample. The results of the research showed that the administrative obstacles have been at the forefront of the obstacles that prevent the application of TQM in all of Al-Yarmouk Teaching Hospital and College of administration and Economics, while the obstacles of human resources were in the first place for the Rafidain Bank. Also, the financial obstacles had a priority among the other obstacles in Al-Karkh/1 Directorate of Education, whereas the environmental obstacles has topped in the International Palestine Hotel. So the researcher recommends organizations surveyed to start the treatment and removal of TQM obstacles depending on their own priority.